TRANSFORMASI PANGURASON DARI RITUAL KE SENI PERTUNJUKAN - Sivalis Diana Sari Diana Sari; Nurwani Nurwani (Gesture: Jurnal Seni Tari, 2018)
ABSTRACT This study discusses the Transformation of Pangurason Performing Arts Ritual. Describes the presentation of Pangurason tortors in the transformation of saucers to the Batak Toba Society in Samosir, and also describes the transformation of Pangurason tortors in the art of tortor cup performances.The theory used in this research is Ritual theory, Transformation, presentation theory form. The time used in this study is during (two months), which starts from October to December 2016. The location of this study was conducted in Pangururan Government of Samosir Regency. The population in this study were artists who knew about Pangurason and the samples were all actors involved in tortor Pangurason and actors involved in tortor bow transformation, data collection techniques including observation, interview, literature study, and documentation, then analyzed by descriptive method qualitative.Based on the data collected, it can be seen that Pangurason is a cleansing or purification of a place that has been considered sacred, so that the place is far from distress, and not disturbed by evil spirits. Formerly when Pangurason was used because at that time, the place wanted to be disturbed by evil spirits, then sibaso or shaman made a ritual to reject the reinforcements, by making a bowl of water, kaffir lime and banyan leaves.The transformation transforms the form of ritual presentation into the performing arts and uses the media or property of the saucer as an attraction in the tortor cup art show. Keywords: Transformation, Pangurason Ritual, Performing Arts